ANALISIS TINDAK TUTUR ILOKUSI PADA PEMBELAJAR BAHASA JEPANG DALAM KLUB BAHASA NIHONGO DE SHABEROUKAI DI MEDAN - Nasution , Laraiba; Sonaria Hasibuan, Annalisa (Kagami : Jurnal Pendidikan dan Bahasa Jepang, 2019)
This study examines the analysis of illocution speech acts in Japanese language learners in the "Nihongo de Shaberoukai" language club in Medan. The problem of this research is (1) What types of speech act of illocution is contained in Japanese learner's speech in the "Nihongo de Shaberoukai" language club in Medan. (2) The function of speech act illocution is contained in the Japanese learners speech in the "Nihongo de Shaberoukai" language club in Medan. The purpose of this study is to describe and describe the type and function of speech acts of illocution whether contained in the Japanese language learners in the language club "Nihongo de Shaberoukai" in Medan. The theories used in this research is Searle's speech act theory. The methodology used in this research is descriptive qualitative method, the last is heuristic analysis technique, recording technique and writing technique and technique of data analysis is method of pragmatic padan. The results of the findings in this study 1. Types of speech acts illocution contained in this study is directive, representative, declarative, commissive and expressive. 2. Functions of speech acts contained in this study is a function of speech act directive commands, representative show place, declarative banning, commissive promise. and expressive thankful.